KAJIAN HUKUM ATAS GADAI TANAH DALAM MASYARAKAT MINANGKABAU DI KECAMATAN SUNGAYANG SETELAH BERLAKUNYA UNDANG-UNDANG NO. 56/PRP/1960 TENTANG PENETAPAN LUAS TANAH PERTANIAN - REFLIZA REFLIZA (PREMISE LAW JURNAL, 2015)
Pawn land is one land transaction is still there and needs of indigenous people in Indonesia, including customary laws Minangkabau. Where the land transactions carried out by a lien in Minangkabau society, especially in the District Sungayang where there are many transactions that have been going on for decades, both orally and in writing. Reason for people still do pawn transaction is for medical expenses, the cost of school / college kid / nephew. Who becomes the object of a pledge, not only rice fields, plantations, trees. But the fish pond and a motor vehicle can be the object of a pledge, and in a letter made ​​lending and borrowing transactions, but the shape of the letter is a letter of lien. And if there is a dispute lien, then the solution must be done gradually , first done with deliberation, if it can not be resolved through new Adat Nagari ( KAN ), if it can not be resolvedthrough the NAC, the new through the local District Court . Keywords: Pawn Land, Minangkabau Community, Law No. 56/Prp/1960.